Performance of an improved breed of common carp - Amur (Hungarian strain) in the North-eastern hill state of Meghalaya, India - Das, S. K. (Indian Journal of Fisheries, 2018)
Common carp (Cyprinus carpio Linnaeus, 1758) is an important fish species for aquaculture in the North-east hill Region (NEH) of India. However, in recent years, the growth performance of the existing stock of common carp has been a major concern. In an effort to improve fish production from farmers’ ponds and to evaluate the performance of the breed in mid hill condition, a genetically improved breed of common carp, Amur (Hungarian strain) was introduced in Meghalaya in 2010. Fingerlings of Amur common carp (weight 14.5 g and length 10.5 cm), reared under mid-altitude conditions in the fish farm of the ICAR Research Complex for North-eastern hill (NEH) Region, Barapani, Meghalaya, attained maturity in about 14 months period. The first breeding trial with this newly introduced variety was conducted successfully in March 2011 when the atmospheric temperature ranged between 16.0-18.30C. The fertilised eggs hatched in 78-83 h (water temperature 19.0-22.80C and pH 6.5-6.8). Three year studies revealed the performance of Amur common carp is superior over the local existing breed in farmers ponds under the mid hill conditions.